Adaptive noise suppression filter based integrated voltage and frequency controller for two‐winding single‐phase self‐excited induction generator. Issue 8 (1st November 2014) - Kalla, Ujjwal Kumar; Singh, Bhim; Murthy, S.S.
Abstract : In this study, an adaptive noise suppression filter based control algorithm is proposed for integrated voltage and frequency controller (IVFC) of a speed governor‐free hydro turbine driven single‐phase self‐excited induction generator (SEIG). A voltage source converter (VSC) is employed to control the terminal voltage of SEIG with adjustable reactive power. It also mitigates the harmonics injected by non‐linear loads in the SEIG system. A resistive dump load with a chopper is connected at dc‐bus of VSC. The dump load is controlled to regulate the system frequency at varying loads and mechanical power input to the unregulated micro hydro turbine during seasonal changes. The frequency estimation and phase shifting technique is used for frequency estimation and for generation of quadrature signal of point of common coupling voltage. The proposed IVFC is designed, developed and implemented using a digital signal processor for a two‐winding single‐phase SEIG of 5 kW rating and test results are presented to demonstrate its performance under steady state and dynamic conditions.